Introduction to CCXML call control for voiceXML applications. - Seth, Hitesh
When building interactive voice recognition applications, we are inevitably faced with the challenge of providing advanced telephony call-control capabilities. In some scenarios we'd like to bridge two calls for a conferencing application, in others we'd like to provide basic call routing so the caller can be connected to an appropriate customer service agent, make outbound calls and the like. VoiceXML doesn't really provide these advanced call-control and telephony features.